The role of a death and grief festival in cultivating awareness of serious illness, death, and bereavement at university: A qualitative study of students’ and staff’s motivations and experiences with Compassionate Week activities - Hanne Bakelants; Sarah Dury; Kenneth Chambaere; Luc Deliens; Steven Vanderstichelen; Filip Van Droogenbroeck; Joachim Cohen (Palliative Care and Social Practice)
Background: At different points in our lives, regardless of our age, gender, location, or socioeconomic background, we all face experiences of serious illness, death, and bereavement. Yet, these topics are often avoided in communities and are predominantly addressed within professional healthcare narratives and practices. In recent years, death and grief festivals have been planned to offer “ways in” to these topics via participatory, creative, educational, and cultural activities. In Belgium, the Vrije Universiteit Brussel (VUB) University hosted its first death and grief festival on the university campus, the Compassionate Week, as a part of the Compassionate University program. Objectives: This study aims to gain a deeper understanding of students’ and staff’s motivations for engaging in the Compassionate Week activities and their experiences of the activities they attended. Design: A qualitative descriptive research design was used to understand the motivations and experiences of students and staff who participated in the Compassionate Week activities. Methods: A total of 94 individual semi-structured interviews were conducted with students and staff. Results: A thematic analysis resulted in three overarching reasons for participating in the Compassionate Week activities: (i) to help with one’s own grief; (ii) to support friends or colleagues; and (iii) to learn about death, bereavement, and the support offered by the university. Additionally, three main types of experience were constructed from participants’ reflections on the activities. The activities (i) created openness to express and share experiences of loss and bereavement, (ii) encouraged compassion (i.e., reflecting on and acting upon the suffering of others), and (iii) raised awareness of serious illness, death, and bereavement as everyday experiences in school and work life. Conclusion: Our study suggests that death and grief festivals, such as the Compassionate Week, can contribute to greater emotional and practical support for students and staff confronted with the experiences of serious illness, death, or bereavement.